On the influence of initial strains in layers on the propagation of torsional waves in a hollow sandwich cylinder (soft core and stiff face layers) - Akbarov, S. D.; Kepceler, T.; Egilmez, M. Mert (SPRINGER, 2013)
Within the scope of a piecewise homogeneous body model, with the use of the three-dimensional linearized theory of elastic waves in prestrained bodies, the effect of initial strains in layers on the dispersion of torsional waves in a hollow sandwich cylinder is studied. Two cases are considered: in Case 1, it is assumed that initial strains exist in only face layers; in Case 2, initial strains occur in all layers of the cylinder. The elasticity relations for layer materials of the cylinder are given through a harmonic potential. A dispersion equation is derived, and an analytical expression is obtained for the limit values of wave propagation speed for low wave numbers. Numerical results are presented and discussed.
Keywords: finite initial strains; wave dispersion; hollow sandwich cylinder; highly elastic material; torsional wave; MATERIAL COMPOUNDED CYLINDER; CIRCULAR-CYLINDER; DISPERSION RELATIONS; Mechanics; Materials Science; Polymer Science